2017
DOI: 10.1186/s13000-016-0591-2
|View full text |Cite
|
Sign up to set email alerts
|

SESN2 correlates with advantageous prognosis in hepatocellular carcinoma

Abstract: BackgroundSESN2 plays important roles in the regulation of cell survival, cell protection, and tumor suppression. However, the relationship between SESN2 expression and the clinicopathological attributes of hepatocellular carcinoma (HCC) is barely investigated.MethodsOne-step quantitative reverse transcription PCR, Western blotting analysis in 15 fresh HCC tissues, and immunohistochemistry (IHC) analysis in a tissue microarray (TMA) containing 100 HCC cases were performed to examine SESN2 expression. Survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…In the present study, sestrin2 was found to be downregulated in 55% of SGC cases relative to non-cancerous and adjacent normal skin. The above data are consistent with the previous studies where differential sestrin2 expression has been detected in cancerous and non-cancerous tissue samples of patients with hepatocellular carcinoma 11. Reduced protein expression of sestrin2 was significantly correlated with poor tumour differentiation and upper eyelid involvement.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, sestrin2 was found to be downregulated in 55% of SGC cases relative to non-cancerous and adjacent normal skin. The above data are consistent with the previous studies where differential sestrin2 expression has been detected in cancerous and non-cancerous tissue samples of patients with hepatocellular carcinoma 11. Reduced protein expression of sestrin2 was significantly correlated with poor tumour differentiation and upper eyelid involvement.…”
Section: Discussionsupporting
confidence: 92%
“…The immunohistochemical staining results for p53 and SESN2 were evaluated on the basis of both percentage positivity and staining intensity 11. The percentage of immunostaining was based on the number of tumour cells showing positivity in 10 high power fields.…”
Section: Methodsmentioning
confidence: 99%
“…SESNs have also been reported to regulate the AMPK/mTOR complex 1 signaling pathway, which is involved in cellular autophagy (56,57). Our study detected decreased expression levels of SESN2 in liver cancer tissues compared with paracancerous tissues (58), which provided clinical evidence that muscone may inhibit tumor development.…”
Section: Discussionsupporting
confidence: 66%
“…In certain types of cancers, SESN2 has shown an important role in being pointed out as a tumor suppressor in lung tumors (19), and the decrease in SESN2 expression has also been correlated with a worse prognosis in liver tumors (20) and the induction of its expression restores apoptotic control in head and neck cell models (21).…”
Section: Discussionmentioning
confidence: 99%